Manajemen Keuangan Berbasis Penerapan Nilai-Nilai Profetik - Saiful Muchlis; Rimi Gusliana Mais; Arif Hartono (Universitas Muhammadiyah Ponorogo, 2022)
This study discusses to study the process of financial management and implementation of prophetic values in financial management at the Office of the Ministry of Religion in Takalar Regency. Prophetic values in this study include shiddiq, amanah, fathanah, and tabligh. This type of research is field research using qualitative research types with interpretive paradigms and using phenomenological and theological research. The results of this study prove that the financial management in the Office of the Ministry of Religion of Takalar Regency has been carried out according to the procedures performed. Knowledge and implementation of prophetic values by financial managers in the Office of the Ministry of Religion in Takalar Regency is realized through the Five Culture of Work of the Ministry of Religion of the Republic of Indonesia, namely Integrity, professionalism, innovation, responsibility, and exemplary. Researchers see the prophetic value in the financial management of Takalar Regency cultivated through the awareness of the managers to always increase their faith by performing the dhuha prayer, and reading the Qur'an before starting activities in the work environment.